Osteopathic Manipulation in the Management of Chronic Pain: Current Perspectives - Licciardone JC; Schultz MJ; Amen B (Journal of Pain Research, 2020)
John C Licciardone,1 Matthew J Schultz,1 Brook Amen2 1Department of Family Medicine, University of North Texas Health Science Center, Fort Worth, TX, USA; 2Gibson D. Lewis Library, University of North Texas Health Science Center, Fort Worth, TX, USACorrespondence: John C LicciardoneUniversity of North Texas Health Science Center, 3500 Camp Bowie Boulevard, Fort Worth, TX 76107, USATel +1817-735-2028Fax +1817-735-0157Email john.licciardone@unthsc.eduAbstract: Chronic pain is a common condition that often interferes with work or other activities. Guidelines support the use of non-pharmacological treatments, such as spinal manipulation, in patients with chronic pain. Osteopathic physicians in the United States are uniquely positioned to manage chronic pain because their professional philosophy embraces the biopsychosocial model and they are trained in the use of osteopathic manipulative treatment (OMT) to complement conventional medical care. This narrative review provides current perspectives on the osteopathic approach to chronic pain management, including evidence for the efficacy of OMT based on systematic searches of the biomedical literature and the ClinicalTrials.gov database. Men, persons with low levels of education, and non-White and Hispanic patients are significantly less likely to have received OMT during their lifetime. Patients with low back and neck pain are most likely to be treated with OMT, and osteopathic manipulative medicine specialty physicians and family medicine physicians most often use OMT. However, many osteopathic physicians report using OMT infrequently. Although OMT is considered safe, based on millions of patient encounters over more than a century, there is limited evidence on its efficacy in treating chronic pain. The lone exception involves chronic low back pain, wherein there is evidence from systematic reviews, a large clinical trial, and observational studies. There is lesser evidence to support cost effectiveness and patient satisfaction associated with OMT for chronic pain. The only clinical practice guideline established by the American Osteopathic Association recommends that OMT should be used to treat chronic low back pain in patients with somatic dysfunction. Given the philosophy of osteopathic medicine, universal training of osteopathic physicians to use OMT, and national guidelines supporting non-pharmacological treatments for chronic pain, it is unclear why OMT use is reported to be remarkably low in physician surveys.Keywords: osteopathic manipulative treatment, chronic pain, somatic dysfunction, randomized controlled trial, cost effectiveness, patient satisfaction